Answer:
Hence, the rate of change of f(x) from x=1 to x=3 is given by:
-4
Step-by-step explanation:
We have to find the rate of change of the function f(x) from x=1 to x=3 which is defined as:
[tex]f(x)=-(3)^{x-1}+3[/tex]
The rate of change of the function f(x) from x=1 to x=3 is given by:
[tex]\dfrac{f(3)-f(1)}{3-1}[/tex]
we know that:
[tex]f(1)=-(3)^{1-1}+3\\\\f(1)=-(3)^0+3\\\\f(1)=-1+3\\\\f(1)=2[/tex]
Similarly,
[tex]f(3)=-(3)^{3-1}+3\\\\f(3)=-(3)^2+3\\\\f(3)=-9+3\\\\f(3)=-6[/tex]
Hence, the rate of change is given as:
[tex]\dfrac{-6-2}{3-1}\\\\=\dfrac{-8}{2}\\\\=-4[/tex]
Hence, the rate of change of f(x) from x=1 to x=3 is given by:
-4